Lipidomic Analysis Reveals the Protection Mechanism of GLP-1 Analogue Dulaglutide on High-Fat Diet-Induced Chronic Kidney Disease in Mice - Yeung, Martin Ho Yin; Leung, Ka Long; Choi, Lai Yuen; Yoo, Jung Sun; Yung, Susan; So, Pui-Kin; Wong, Chi-Ming (Frontiers in Pharmacology, 2022)
Many clinical studies have suggested that glucagon-like peptide-1 receptor agonists (GLP-1RAs) have renoprotective properties by ameliorating albuminuria and increasing glomerular filtration rate in patients with type 2 diabetes mellitus (T2DM) and chronic kidney disease (CKD) by lowering ectopic lipid accumulation in the kidney. However, the mechanism of GLP-1RAs was hitherto unknown. Here, we conducted an unbiased lipidomic analysis using ultra-high-performance liquid chromatography/electrospray ionization-quadrupole time-of-flight mass spectrometry (UHPLC/ESI-Q-TOF-MS) and matrix-assisted laser desorption/ionization mass spectrometry imaging (MALDI-MSI) to reveal the changes of lipid composition and distribution in the kidneys of high-fat diet-fed mice after treatment with a long-acting GLP-1RA dulaglutide for 4 weeks. Treatment of dulaglutide dramatically improved hyperglycemia and albuminuria, but there was no substantial improvement in dyslipidemia and ectopic lipid accumulation in the kidney as compared with controls. Intriguingly, treatment of dulaglutide increases the level of an essential phospholipid constituent of inner mitochondrial membrane cardiolipin at the cortex region of the kidneys by inducing the expression of key cardiolipin biosynthesis enzymes. Previous studies demonstrated that lowered renal cardiolipin level impairs kidney function via mitochondrial damage. Our untargeted lipidomic analysis presents evidence for a new mechanism of how GLP-1RAs stimulate mitochondrial bioenergetics via increasing cardiolipin level and provides new insights into the therapeutic potential of GLP-1RAs in mitochondrial-related diseases.